An epitranscriptomic mechanism underlies selective mRNA translation remodelling in melanoma persister cells - Shensi Shen (Nature Portfolio, 2019)
Melanoma persister cells are tolerant to anti-BRAF and anti-MEK inhibition and can trigger cancer relapse. Here the authors show that a subset of N6-methyladenosine modified mRNAs is translationally activated in persister cells. This preferential translation can be abrogated via eIF4A inhibition.